Cyclic Testing of Bolt-Weld Joints Reinforced by Sleeves Connecting Circular CFST Columns to Steel Beams - Yonghong Bu; Qi Yang; Yihong Wang; Dongfang Zhang (Advances in Civil Engineering)
This study examined the design of joints reinforced by sleeves for connecting circular concrete-filled steel tube columns to steel beams. Six half-scale specimens, including four bolt-weld joints reinforced by sleeves and two bolt and stiffened end-plate joints, were designed and tested under cyclic loading to evaluate the seismic behavior of these joints. The joint construction and beam-column stiffness ratio were taken as the main parameters in the tests. The seismic behaviors, including the failure modes, hysteretic curves, ductility, strength and stiffness degradation, and energy dissipation, were investigated. The experimental results showed that no obvious bolt loosening, fracture, or widespread weld cracking appeared in the joints reinforced by sleeves. Furthermore, the joint strength and stiffness were markedly increased by the sleeves in the joint core area. Overall, most specimens exhibited full hysteresis loops and excellent ductilities, the equivalent viscous damping coefficients were 0.263∼0.532, and the ductility coefficients were 1.77∼3.42. The interstory drift ratios satisfied the requirements specified by technical regulations. The connections of these types exhibit favorable energy dissipations and can be effectively utilized for building construction in earthquake-prone areas. This research should contribute to the future engineering applications of concrete-filled steel tube to composite structure.